SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN LAPTOP MENGGUNAKAN METODE FUZZY DAN METODE TOPSIS - Taufik Kurnialensya (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
Before buying a laptop, you need to pay attention to the specifications and standards that are tailored to your needs and requirements. Some of the standards and requirements include looking at several aspects of the criteria including RAM (random access memory), laptop prices, hard disk capacity, processor, screen size, VGA (video graphic adapter), battery power, availability of spare parts, laptop weight, distance to service centers, long warranty. The fuzzy method is an algorithm used to find a value that is still vague and also linguistic, using the TOPSIS algorithm (Technique for Order by. Similarity to Ideal Solution) to support calculations in decision-making. Determination in using the TOPSIS algorithm results from careful calculations. From the results of calculations using the TOPSIS algorithm, the total ideal positive and negative ideal values ​​are generated with the following ratings: laptop 5 with a value of 4.637 in rank 1, laptop 3 with a value of 4.174 in rank 2, laptop 4 with a value of 4.077 in rank 3, for laptop 1 with a value 3.880 is ranked 4th, and laptop 2 with a value of 3.472 is ranked 5th. Keywords: fuzzy, TOPSIS, laptop.